Towards a full understanding of water splitting in photosynthesis - James Barber (International Journal of Photoenergy)
The capture and conversion of solar radiation by photosynthetic organisms directly or indirectly provides energy for almost all life on our planet. About 2.5 billion years ago a remarkable biological “machine” evolved known as photosystem two (PSII). This machine can use the energy of visible light (actually red quanta of ∼ 1.8 eV) to split water into dioxygen and “hydrogen”. The latter is made available as reducing equivalents, ultimately destined to convert carbon dioxide to organic molecules. In PSII, the “hydrogen” reduces plastoquinone (PQ) to plastoquinol (PQH2). The water splitting process takes place at a catalytic centre composed of 4 Mn atoms and the reactions involved are chemically and thermodynamically challenging. The process is driven by a photooxidised chlorophyll molecule (P680•+) and involves electron/proton transfer reactions aided by a redox active tyrosine residue situated between the 4 Mn cluster and P680. The P680•+ species is generated by light induced rapid electron transfer (a few picoseconds) to a primary acceptor, pheophytin a, before being transferred to PQ acceptors. Electron and x-ray crystallographic studies are now starting to reveal the structural basis for these reactions including the light harvesting processes. The 4 Mn atom-cluster has been visualised as have the chlorophylls that constitute P680. The scene is now set to fully elucidate the reactions of PSII and possibly mimic them in an artificial photochemical system that could split water and produce hydrogen.